2018
DOI: 10.1097/mpg.0000000000001861
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin Test Performed at Home

Abstract: PIBD patients and their families were interested in FC home monitoring and willing to adopt testing as a part of their disease management, but this approach requires thorough guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…The possibility to measure calprotectin with a smartphone at home is a novelty in IBD-care. We identified three recently published studies on the IB Doc home test, [7, 9, 10] and one on the CalproSmart home test. [11] All studies showed acceptable agreement between home test and companion ELISA in the low range and lack of agreement in the high range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility to measure calprotectin with a smartphone at home is a novelty in IBD-care. We identified three recently published studies on the IB Doc home test, [7, 9, 10] and one on the CalproSmart home test. [11] All studies showed acceptable agreement between home test and companion ELISA in the low range and lack of agreement in the high range.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in this study we report an a priori decision of acceptable limits of difference for adequate interpretation of the Bland-Altman plot, a feature that was absent in three of the aforementioned studies. [911] Precision is of utmost importance in the low ranges of calprotectin values, where small deviations can lead to misclassification of disease activity and wrong treatment decisions. In our practice, however, imprecision in the high range is less of an issue, since we consider each calprotectin result >500 μg/g to reflect active disease, irrespective of the absolute concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The IBDoc (Laboratories AG, Baselstrasse 55, CH-4124 Schönenbuch, Switzerland) home kit was selected owing to its wide usage in various countries, including some National Health Service (NHS) trusts, [5][6][7][8] and as a kit which, when tested, was found to agree with ELISA tests at calprotectin levels <500 µg/g. 9 10…”
Section: Summary Boxmentioning
confidence: 99%
“…An investigation into the feasibility of home FC testing concluded that 80% of parents felt this method would improve disease management, however, the practicality of using them was difficult for over half. 32 This method of testing allows for greater patient empowerment with reduced embarrassment, especially for adolescents, perhaps leading to better compliance. The technology also allows smartphone apps to communicate results directly and immediately to the patient's MDTs, increasing efficiency and potentially also the speed of clinical reaction to elevated results.…”
Section: Role Of the Mdtmentioning
confidence: 99%